Escravidão contemporânea – combate - Leão, Ione Maria Barreto (2016)
This work aims to provide a brief contextualization about the kind of labor that is still performed in degrading conditions, thus constituting a violation of a number of constitutional principles, chiefly human dignity, and described as modern day slave labor. The research of doctrines and articles revealed that despite being refuted by many persons, slave labor exists and its dissemination across our territory is unchallenged - mainly in the poorest regions - and centered in rural areas. Furthermore, after the publication of the Constitutional Amendment No. 81, which altered Article 243 of the Federal Constitution to allow the confiscation of property from individuals or corporations who, as employers, are caught committing the crime of contemporary slavery as defined by Article 149 of the Criminal Code, the Brazilian Congress acknowledged the existence of workers submitted to undignified labor conditions. The latter is used to define the crime and include, among other hypotheses, excessive working hours, degrading work and forced labor. Research results have also identified the main means to combat contemporary slave labor focusing on the Public Labor Prosecutor who has relentlessly fought to completely eradicate this social injustice that taints our society, and negatively reflects on social and economic progress as well as before international agencies. The research concluded that a lot has been done to improve this situation. However, given the defiant attitude of some employers on committing the crime described by Article 149 of the Criminal Code, there is hope that the alteration provided by Article 243 of the Constitution, together with the other forms of combat, we will be able to achieve - in a very short time - a radical change in the reported numbers of workers submitted to undignified labor practices in total violation of fundamental principles, essentially human dignity, the pillar of our Constitution